Upaya Meningkatkan Gerak Lokomotor Siswa Sekolah Menengah Atas Dalam Pembelajaran Atletik Melalui Metode Bermain - Panji Abdul Azis; Ega Trisna Rahayu; Febi Kurniawan (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of the play method in improving students' locomotor motion in athletic learning at SMA 1 Telukjambe Barat, this study uses experimental method and using a quantitative approach with a sample of 30 students of class VIII 2 . In learning, the sampling technique is carried out using purposive sampling. In this technique, a sample is determined with certain considerations, namely the 11th grade students who, according to the researchers' considerations, still remember more clearly the reasons and processes when performing locomotor movements, based on the results of the data. processing that has been analyzed, the answers to the hypotheses that have been previously proposed by the researcher has been obtained. It results and conclusions about efforts to improve the locomotor motion of senior high school students through athletic learning using the play method at SMA 1 Telukjambe Barat. Has an influence on student locomotor movement, especially in athletic learning activity material. This is proven by conducting research that carried out during the learning of athletic learning materials. The method of playing in learning activities becomes more effective. fun and interesting, besides using the play method in physical education learning is very effective and efficient given to students in carrying out physical education learning activities at SMA 1 Telukjambe Barat.